Re-Engaging Individuals & Societies for Structural Evolution: A Brain Health Equity Neuropsychology Research Framework. (29th March 2023) - Díaz-Santos, Mirella; González, David Andrés; Henry, Samantha K; Vuong, Kevin Dat; Strutt, Adriana Macias
Abstract: Objective: A brain health equity neuropsychology research framework (NRF) is crucial to the anti-racist movement in cognitive assessments. Universalist interpretation of neuropsychological tools contributes to systemic disparities, and there is a need for a clear conceptual framework for disentangling the direct and indirect impact of social determinants of health (SDH) on brain-behavior relationships and neuropsychological performance. The aim of this paper is to present a NRF anchored in the principles of brain health and health equity that is inclusive, and can be implemented across racially and ethnically diverse communities. Methods: The Re-engaging Individuals and societies for Structural Evolution (RISE) NRF aims to address this via a two-pronged approach: 1. Focusing on community engagement and recruitment and retention of individuals and societies typically not equitably represented in brain health studies, and 2. Integrating the conceptual structure of individual, community, and SDH, while considering the broader historical and current structures that differentially shape these. Results: The proposed RISE NRF is dynamic and multidirectional. It identifies barriers and proposes strategies to engage communities and diversify recruitment. It identifies evidence-based guidance on non-cognitive determinants of health to include, consider or explore in brain health research. Conclusion: The RISE NRF can guide the development of culturally and linguistically responsive methodologies and assist with clearly conceptualized and contextualized interpretation of neuropsychological tools to foment a transformative science that benefits the brain health of marginalized communities.